Guy Gilchrist's Tiny Dinos playing together : a book of everyday feelings. - Gilchrist, Guy. (New York : Warner Juvenile Books, 1988)
The dinosaurs experience feelings of boredom, curiosity, conceit, happiness, nervousness, and confidence when they get together to play a game of baseball.
Keywords: Emotions -- Fiction; Baseball stories; Dinosaurs -- Fiction; Stories in rhyme